Creating New Spaces That Foster Students' Emotional Well-Being; Breakthrough Strategies in Curriculum Management Based on Mental Health - Kikik Windia Sari; Akmal Mundiri; Moses Adeleke Adeoye (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
The curriculum also causes problems with student growth and development in schools. Complaints about students’ mental health have recently emerged as an issue among education observers. Content that is too difficult or irrelevant to students’ daily lives can cause confusion, tension, and a lack of motivation to learn. This study aims to understand how the implementation of a curriculum centered on students’ mental health. This study uses a qualitative type,  with a case study approach. Data were collected through observation, interview, and documentation techniques. Data were analyzed using Miles, Huberman, and Saldana data analysis techniques. The results of the study showed that the implementation of a curriculum centered on students’ mental health was carried out through activities for morning discussions, activities using innovative games to help students emotionally, cooperative activities in building bridges, monitoring activities, and the use of camping activities to develop social and emotional skills. These activities have a positive impact on students’ mental health. These findings confirm that integrating mental health-based activities in the curriculum supports students' psychological well-being but also improves students' social and academic skills. Implikasi, Novelty.